Studi Banding Infeksi Luka Operasi Caesar dan Implementasi Peraturan Kementerian Kesehatan - Friza Novriansyah; Kusbaryanto (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
The global rise in cesarean section (CS) deliveries has increased the risk of surgical site infections (SSI), a leading cause of maternal morbidity and mortality. To address this issue, Indonesia introduced Ministry of Health Regulation No. 40 of 2022, which sets technical standards for hospital buildings, infrastructure, and medical equipment. This study aimed to assess the impact of implementing the regulation on SSI incidence among CS patients by comparing RSU PKU Muhammadiyah Gubug, which has implemented the regulation, and RS Aisyiyah Kudus, which has not. A cross-sectional mixed-methods study was conducted from January to April 2025 involving 41 CS patients (10 at RSU PKU Muhammadiyah Gubug and 31 at RS Aisyiyah Kudus). Quantitative data were analyzed using descriptive statistics and independent-sample t-tests, while qualitative data were obtained through semi-structured staff interviews. Results showed no SSI cases at RSU PKU Muhammadiyah Gubug, while one case (3.23%) occurred at RS Aisyiyah Kudus, with no statistically significant difference (p = 0.251). Compliance at RSU PKU Muhammadiyah Gubug was supported by staff training and infrastructure upgrades, whereas RS Aisyiyah Kudus faced financial and resource constraints. Although the difference in SSI incidence was not significant, the findings suggest that regulatory adherence positively contributes to infection prevention. Larger multicenter studies are needed to validate these results and strengthen evidence for long-term infection control strategies.